Control of stepping downstairs for humanoid robot based on dynamic multi‐objective optimization. (14th September 2020) - Ke, Wende; Bai, Yan; Li, Huazhong; Chen, Ke; Yuan, Quande
Summary: The dynamic multi‐objective optimization has important applications in many fields, especially for the multi‐issues about trading‐off problems. Herein the dynamic multi‐objective optimization problem is applied in the stepping downstairs motions of humanoid robot in which three sub‐optimization problems are proposed. First, the motion analysis of the robot's stepping downstairs motion is processed and the dynamic multi‐objective optimization algorithm is introduced as well. The optimization algorithm is changed by the mutation mode of the traditional genetic algorithm. Second, the motion analysis of the robot's stepping downstairs motion is carried out. Finally, the walking speed function, walking stability function, and electrode cost function are obtained. The effects were validated through simulating experiments.